Editorial to the special issue on JCDL 2022 - Philipp Mayr; Annika Hinze; Philipp Schaer (International Journal on Digital Libraries, 2024)
This special issue features the selected works of authors who have presented papers at the 2022 iteration of the Joint Conference on Digital Libraries (JCDL) in Cologne, Germany. The motto of the conference was “Bridging Worlds” and was run as a fully hybrid event. Ten papers covering all aspects of Digital Libraries, namely Natural Language Processing, Information Retrieval, User Behavior, Scholarly Communication, Classification, Information Extraction are included in this issue.
Keywords: 000; Digital libraries; Natural language processing; Information retrieval; User behavior; Scholarly communication; Classification; Information extraction